Political communication through a qualitative lens - Mokhtar, Aida (Penerbit UKM, 2017)
With the growth of the political communication discipline as the goal, the qualitative inquiry, in a field that is dominated by the quantitative inquiry, has been recommended to be placed alongside quantitative research in some literature. This is not a novel recommendation. The mixed methods approach in the pursuit of theoretical understanding is emulating the traditional political communication research practices of previous scholars. The discipline’s growth should be spurred by answering new research questions, developing old theories, innovating new theories and making new recommendations that would benefit from the interpretive paradigm of the qualitative inquiry. There is greater engagement between political actors with the advent of social media, an inevitable importance of image and identity in political brand communication, inequality in obtaining political messages, the interdisciplinary nature of political communication and the political public sphere – all these characterized political communication. Political communication benefits from the interpretive paradigm by allowing an examination of perspectives from participants encompassing insider information obtained from political parties and the discourse analysis of political actors on social media that underscores the profoundness of qualitative interpretations.